Rethinking Multilevel Governance as an Instance of Multilevel Politics: A Conceptual Strategy. Issue 1 (2nd January 2016) - Alcantara, Christopher; Broschek, Jörg; Nelles, Jen
Abstract: This paper introduces a new approach to the comparative analysis of multilevel governance (MLG). Using water governance in North America as an illustrative example, it advances an innovative approach for scrutinizing the varieties of actor constellations in multilevel settings. While MLG is commonly conceptualized rather broadly as a system, we define MLG instead as an instance of a specific actor configuration that can rigorously be distinguished from other configurations, most notably intergovernmental relations (IGR). With this more conceptually bounded classification, we suggest that scholars can now more fruitfully engage in systematic analyses of MLG and IGR across different types of political systems (e.g. unitary, federal and supranational). Our hope is that this paper will provide some much needed conceptual and analytical clarification to an increasingly nebulous debate on what MLG actually is and what it means for students of political science, public policy and public administration.